(untitled) (Journal of the College of Basic Education, 2022)
Make-up considers one of the important elements that contribute to child excitement. It creates a continuity in his imaginations full of emotional connotations which allow his perceptions to be transformed into aesthetic values ​​through different visual means, which are linked in their pattern the correlation of color with makeup and with the help of lighting and its organized projections on the actors and to achieve the color system in child theater make-up. For this reason, the researcher dealt with in the first section (the color concept and functional work in the child’s theater), the color effects on the sensory process its. The color was also classified according to the chromatic values ​​and showed color and the extent of interaction in producing a pictorial complementarity in order to obtain a drama clarification and convert it into an expressive energy with systematic excitement on the child. The second section includes (the functional tasks of make-up art in child theatre). The researcher discussed make-up types and tried to renew a group of lighting colors and linked them to reach to excitement process, attract attention and allow to child imagination to interact with the theatrical presentation and its plastic vocabulary. The researcher proved the most important criteria of the theoretical framework, The most important results that the researcher came out with are: The characters who assume their roles with the help of colors and make-up, effects on building the child’s character through anticipation and surprise. The research ends with a list of references and an English abstract.